Response of estuarine meiofauna communities to shifts in spatial distribution of keystone species: An experimental approach - Citadin, Monica [UNESP]; Costa, Tânia M. [UNESP]; Netto, Sérgio A. (Elsevier, 2018)
Current climate change directly affects species distribution by altering their physical environment and indirectly by altering interspecific interactions. The geographical distribution of fiddler crabs, keystone species of intertidal estuarine sediments, is supposed to expand poleward as a response to climate change. We experimentally investigate whether the introduction of a new species of fiddler crabs, where another different species already occurs, may affect the structural and functional composition of meiobenthic communities in intertidal areas. In order to disentangle the effect of abundance from species identity, we set up two indoor experiments (substitutive and a partial additive design) manipulating the diversity and density of two keystone species, Leptuca uruguayensis and L. leptodactyla. The results showed that the increase of the diversity keystone species did not impact any measured descriptors of nematode assemblages. By contrast, high density of keystone species, independent of the species, strongly affected the meiofauna total density, and the density of numerically dominant nematode genera. The results did not reveal any functional change in the meiofauna. Our experiments, designed to mimic the indirect effects of range expansion showed that while increasing diversity of functionally redundant keystone species had no effect on preys, increasing density negatively affected the structure of intertidal habitats.
Keywords: Fiddler crab; Global warming; Meiofauna; Nematodes; Range shifts